A large variety of clinical features and concomitant disorders in celiac disease – A cohort study in the Netherlands. Issue 5 (May 2016) - Spijkerman, Marleen; Tan, Ineke L.; Kolkman, Jeroen J.; Withoff, Sebo; Wijmenga, Cisca; Visschedijk, Marijn C.; Weersma, Rinse K.
Abstract: Background and aims: Celiac disease (CeD) is a gluten triggered, immune-mediated disease of the small intestine. Few clinical cohort descriptions are available, despite the diverse clinical picture. This study provides an overview of a large Dutch CeD cohort focusing on presenting symptoms, co-occurrence of immune mediated diseases (IMD) and malignancies. Methods: We performed a retrospective study in a Dutch university and a non-university medical hospital and included only biopsy proven (≥Marsh type 2 classification) CeD patients. Results: 412 patients were included, selected from 9468 small-bowel biopsy pathology reports and financial codes. Classical symptoms were present in approximately one third of the cohort (diarrhea (37.4%), fatigue (35.0%), weight loss (31.6%), abdominal pain (33.3%)). Atypical symptoms as constipation (10.4%) and reflux (12.4%) were reported as well. 11.7% was diagnosed without reported symptoms. In 25.2% concomitant IMD occurred (most prevalent: type 1 diabetes mellitus (4.9%), microscopic colitis (4.9%), immune mediated-thyroid disease (4.1%)). CeD patients with a concomitant IMD were diagnosed at a significantly higher age compared to those without ( P  = 0.002). Malignancies occurred in 53 cases (12.9%), including eight Enteropathy Associated T-cell Lymphomas. Conclusion: This is the first study describing a CeD cohort in such detail in the Netherlands and highlights the clinical heterogeneity and importance of screening for concomitant diseases in CeD.